A matter of risk : insurance in Malaysia, 1826-1990 - Lee, Kam Hing (NUS Press, 2012)
The insurance industry in Malaysia is a large and important sector of the economy in terms of capitalisation, business turnover, assets, and the number of employees. It was integral to early Western economic expansion into Malaya, underwriting shipping, mining, and plantation ventures to protect entrepreneurs from excessive risk. The scope of the insurance business then broadened to cover fire risks, motor insurance, and workmen's compensation, while war risk coverage helped ensure that the economy continued to function during the 1940s and 1950s. After 1957, the social and political environment of independent Malaysia offered new directions for the insurance industry. A Matter of Risk shows how insurance companies established themselves in an unfamiliar environment, marketed new products, responded to diverse demands and safeguarded market share and profit against competition. Local firms faced a major challenge as overseas insurance companies moved from agency offices to the setting up of branches, taking over or collaborating with existing companies, and eventually incorporating themselves as local companies. The study looks at the role of tariff associations and insurance trade organisations such as Persatuan Insuran Am Malaysia (General Insurance Association of Malaysia) in maintaining order in the industry through self-regulation.